Pengaruh Pelatihan Dasar Kepemimpinan terhadap Kepercayaan Diri dan Kemampuan Problem Solving Anggota Pramuka - Febrihariyanti, Dwi Nowo (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This study aims to identify and evaluate whether basic leadership training influences on increased self-confidence and problem solving ability of scout members. The subject of this research are all members of the Board of shelves scout Raden Pratanu-Syarifah Ambami Frontline 09.73 - 09.74 based at SMA Negeri 1 Arosbaya numbered 60 people. Experimental design used was a quasi experimental, one-group pretest-posttest design. Data were collected by scales of self-confidence and problem solving ability. Such data as the results of the pretest scores and posttest. The collected data were analyzed by t-test. The result of study indicated that the basic leadership training affects on increase self-confidence and problem solving ability of scout members.Keywords: basic leadership training, self-confidence and problem solving ability